Literary Formation And Dynamics Of Social Change As Exemplified By Mark Twain And Muqimi - Saparniyazov Omirbek Nukusbayevich (Open Academia, 2025)
This article comparatively analyzes literary formation and the dynamics of social change in Western and Eastern literature through the works of Mark Twain and Muqimi. Both authors' lives and works emerged under specific historical and social conditions, and their artistic heritage illuminates the social, cultural, and moral problems in their respective societies. The research extensively covers the stages of literary formation, the application of realism and satirical elements, linguistic issues in translation practice, and connections with folklore and journalistic traditions. The analysis results reveal artistic approaches aimed at forming social consciousness in the works of Mark Twain and Muqimi
Keywords: Mark Twain; Muqimi; literary formation